My animal kingdom : all about pandas, 3. (Richmond Road, London : DeAgostini UK Limited, 2001)
Discover the world of nature with cuddly new friends. Meet Pandora and Paw Paw in 'All About Pandas' - a fun and fact.
Keywords: Pandas--Juvenile literature; Animals--Juvenile literature